Características agronômicas e teor de óleo de diferentes genótipos de canola semeados em diferentes épocas e densidades - Melgarejo Arrúa, Milciades Ariel (2016)
Canola (Brassica napus L. var. oleifera) when grown at different spacings between rows and / or spacing between plants may favor maturation uniformity and increase productivity. Another important aspect of the crop is a definition of the adaptation period of sowing, which is of great importance to enable full growth, development and productivity. In order to generate information for the quality of a choice of canola hybrids more adapted as better sowing times and as better plant populations, three experiments were installed in which they were evaluated as agronomic characteristics and grain oil content. The experiments were conducted in the experimental area of the Universidade Estadual do Oeste do Paraná (UNIOESTE) in Marechal Cândido Rondon-PR, in the years of 2013, 2014 and 2015. In the first experiment Hyola 61 canola hybrid was sown in different spacings between As lines and plant densities in the lines. The experimental design was used for randomized blocks, in arrangement of subdivided plots, with four replications. In the plots, row spacings (17, 34, 51 and 68 cm) were used and, in the subplots, plant densities (15, 30, 45 and 60 plants per square meter) were used. There is no second experiment for the canola generators Hyola 401, Hyola 76, Hyola 61, Hyola 433, Hyola 501, Hyola 571CL, Hyola 575CL, Hyola 474CL, Hyola 555TT, Hyola 656TT, Hyola 559TT, W8006 and H92002. The experimental design was used for randomized blocks with four replicates. As the plots were composed of four rows in 0.45 m, with 5 m in length, without weekly on May 8, 2015. There is no experience of five types of canola and two dates of sowing. The experimental design was a randomized complete block design (2x5), with four replications, with two sowing dates: April 28 and May 28, 2014, and April 20 and May 20, 2015. Five genotypes of canola: Hyola 76, Hyola 433, Hyola 61, Hyola 571 and Hyola 411. As plots were composed of six binders in 0.45 m with 5 m in length. Regarding the experiment with different row spacings and plant densities, in the year 2013, the average pods size per plant was 203 units, a corn mass of 3.8 grams and a mean productivity of 1290 kg ha-1. Significant interaction (p < 0.05) between spacing and density was observed for a plant height variable and number of grams per pod. In 2013, an average of 203 siliquas per plants were obtained. As early as 2014, the average number of pods was 126 units, with an average yield of 899 kg ha-1. Significant interaction (p < 0.05) was observed between the spacing and a density for a variable mass of corn and oil content. Regarding the experiment with 13 genera, significant differences were observed regarding the cycle (p ≤ 0.05) where the genotype Hyola 401, Hyola 50, Hyola 565TT and Hyola 559TT demonstrated the shortest cycle with 129 days and the mass of thousand grains where the genotypes Hyola 76, Hyola 571CL, Hyola 575CL, Hyola 474CL, Hyola 559TT, W8006 and H92002 obtained higher value. No significant differences were observed in the other variables analyzed by the Tukey test at 5% probability. The average grain yield of the tests was 1,518 kg ha-1 and a mean oil quality content of 42.45%. As agronomic characteristics and oil contents were not influenced by genetic tests. In the experiment with 5 genotypes of canola, in 2014, as sowing done on 05/28 obtained 31% more productivity, Hyola 411 obtained the average yield of 1,367 kg ha-1 of canola grains, being 25% higher The average of the other hybrids studied. Already, in 2015 the study with the same materials did not show significant differences in grain yield. 191 From Distr. From Distr. The average oil content on the grains was 39% and also did not detect significant differences between hybrids and time of sowing.